Analisis Pengendalian Kualitas Produk Synthetic Thickener Menggunakan Metode PDCA pada PT X - Rully Nur Dewanti; Dyah Puspitasari Sunaryo Putri; Dadang Kurnia (JURNAL INDUSTRI DAN TEKNOLOGI SAMAWA, 2026)
This study addresses the high defect rate of synthetic thickener products at PT X, which potentially affects product quality and production efficiency. Based on data from January to June 2023, out of 68 production batches, 13 batches (19.11%) were identified as defective, with dominant defects found in the appearance and residue parameters. This research aims to identify the root causes of defects and propose appropriate quality improvement strategies. The study employs the PDCA (Plan-Do-Check-Act) approach, supported by FMEA (Failure Mode and Effects Analysis) and cause-and-effect diagrams. The findings indicate that the main contributing factors originate from material, human resources, methods, machinery, and environmental conditions. The highest Risk Priority Number (RPN) is found in the polymerization process, indicating it as the most critical stage requiring immediate improvement. The application of these methods effectively identifies root causes and provides systematic corrective actions. Therefore, the implementation of PDCA and FMEA is expected to enhance product quality consistency and reduce defect rates in a sustainable manner.